PERANGKAT LUNAK SOLUSI UMUM SISTEM PERSAMAAN DIFERENSIAL LINIER TINGKAT KE-N DENGAN KOEFISIEN KONSTAN - (NIM 23595006), AMIR
Abstract : The thesis consist of a study to find a General Solution of Linear Differential Equation nth-Order System with Constant Coefficient and a prototype for verifying the solution. The software is called SPDLK (Sistem Persamaan Diferensial Linier dengan Koefisien Konstan). A general solution of linear differential equation nth-order with constant coefficient is a general function from computer algebraic method . To obtain the solution, this model uses Cramer method, Muller method and Operator Factorization from A.B. Urdaletova and S.K. Kyrdryaliev. Cramer method is used for solving linear equation system, Muller method is used to find roots of polynomial equation, whereas operator factorization is used to solve linear differential equation with constant coefficient. Structured method is used as the analysis and design method. SPDLK prototype is implemented in Turbo Pascal ver. 7.0